Chondrosarcoma of the maxilla resected using anterior segmental maxillary osteotomy and an open rhinoplasty approach through a 3d-printed bone model: A case report and literature review - Keisuke Yamamoto; Makoto Kurose; Hironari Dehari; Ryota Takashima; Tsuyoshi Okuni; Akira Yorozu; Taka-aki Tokura; Hiromi Nakai; Akihiro Miyazaki; Kenichi Takano (Acta Oto-Laryngologica Case Reports)
Background Chondrosarcoma of the maxilla is extremely rare, requiring complete surgical resection with clear margins. Various surgical approaches have been used for wide surgical resection of chondrosarcomas in the head and neck region. 3D printed bone models are useful surgical and educational tools.Case A 69-year-old man presented with a grade II chondrosarcoma of the maxilla. This tumor was resected by otolaryngologists and dental surgeons using an anterior segmental maxillary osteotomy and open rhinoplasty approach with the assistance of a 3D-printed bone model.Conclusion Chondrosarcomas can be differentiated from chondromas by their higher mean apparent diffusion coefficient (ADC) on diffusion-weighted magnetic resonance imaging. The anterior segmental maxillary osteotomy and rhinoplasty approach, with ideal osteotomy and a good visual field, resulted in wide surgical safety margins, improving patient prognosis.